Association of PTPN22 rs2476601 and EGFR rs17337023 Gene polymorphisms and rheumatoid arthritis in Zahedan, Southeast Iran. (27th January 2013) - Hashemi, M.; Atabaki, M.; Daneshvar, H.; Zakeri, Z.; Eskandari‐Nasab, E.
Summary In this study we aimed to evaluate the possible association of PTPN22 rs2476601 as well as epidermal growth factor receptor (EGFR) rs17337023 gene polymorphism and rheumatoid arthritis (RA) in a sample of Iranian population. This case‐control study was performed on 120 patients with RA and 120 healthy subjects. Genomic DNA was extracted from whole blood and PTPN22 rs2476601 and EGFR rs17337023 polymorphisms were determined using tetra amplification refractory mutation system–polymerase chain reaction (T‐ARMS‐PCR). The results showed that PTPN22 rs2476601 CT genotype as well as rs2476601 T allele was a risk factor for susceptibility to RA (OR=5.89 95%CI = 1.78–19.48, P = 0.004 and OR = 4.78, 95%CI = 1.59–14.35, P = 0.003, respectively). We also found that EGFR rs17337023 AT and rs17337023 TT genotypes were risk factor for susceptibility to RA (OR = 9.94 95%CI = 3.65–26.73, P < 0.001 and OR = 3.66, 95%CI = 1.46–9.15, P = 0.005, respectively). In addition the EGFR rs17337023 T allele was a risk for predisposition to RA (OR = 1.56, 95%CI=1.06‐2.30, P = 0.030). In conclusion, we found an association between PTPN22 rs2476601 and EGFR rs17337023 polymorphisms and the risk of RA in a sample of Iranian population.